Case Report: Lyme Borreliosis and Pregnancy - Our Experience - Trevisan, Giusto; Ruscio, Maurizio; di Meo, Nicola; Nan, Katiuscia; Cinco, Marina; Trevisini, Sara; Forgione, Patrizia; Bonin, Serena (Frontiers in Medicine, 2022)
Lyme Borreliosis (LB) is an infection transmitted by Ixodes sp. ticks. Its early manifestation includes erythema migrans rash. Since the discovery of LB in 1975, the question arose as to whether this infection could be vertically transmitted from mother to fetus during pregnancy, as transplacental transmission has already been known for other spirochetoses, such as syphilis, relapsing fever and leptospirosis. The first confirmed case with positive Lyme serology was described in 1985 in a 28-year- old mother who had acquired Lyme in the first trimester and then developed an erythema migrans rash. Subsequently, transmission of Borrelia burgdorferi sl. in humans from mother to fetus has been documented through identification of Borrelia spirochetes in fetal tissues/and or placenta by various methods including culture, PCR and indirect immunofluorescence. Adverse birth outcomes, which are limited in case of prompt LB treatment, included spontaneous miscarriage, preterm birth and hyperbilirubinemia, but also cardiac involvement and cutaneous angiomas have been documented although rarely. No significant associations were found between adverse outcomes at birth and the trimester of infection. Patients treated for gestational LB had a lower frequency of miscarriages and premature births, as also the frequency of congenital malformations was similar to that observed in the normal population. The recommended treatment for LB in pregnancy is Amoxicillin, 1 g 3 times a day for 14–21 days. In the present study, we report our case series, which includes 11 pregnant women, 6 of which developed erythema migrans during pregnancy (between week 8 and 34), 3 had myoarticular or neurological symptoms and 2 had positive serology, but did not develop any clinical symptoms. Our data stress on the importance of early antibiotic treatment also in seropositive gestating women without symptoms in order to avoid any possible complication to fetus and newborns.